Computational structure revision of a longipinane derivative meridane. Issue 42 (19th October 2016) - Reddy, D. Sai; Kutateladze, Andrei G.
Graphical abstract: Highlights: Misassigned structure of a sesquiterpene meridane is computationally corrected. Besides chemical shifts, J H–H and J C–H are computed with rff to aid in revision. Structure correction necessitated revision of the mechanism of meridane's formation. Abstract: Structure revision of a recently reported longipinane derivative, meridane, was enabled by computations of its NMR spectra. This structural revision necessitates corrections in the originally proposed Wagner–Meerwein mechanism for the formation of meridane.